Intelligence classification and fuzzy optimisation model of people with epilepsy / Siti Rahmah Awang - Awang, Siti Rahmah (Institute of Graduate Studies, UiTM, 2012)
Epilepsy refers to disturbances in the nerves caused by excessive electrical activities taking place in the brain. One of the most challenging problems faced by people with epilepsy (PWE) is finding employment. The objective of this thesis is to identify intelligence profiles of epilepsy patients and to classify their intelligence patterns and characteristics based on a developed intelligence scale, Ability Test in Epilepsy (ATIE©).